Bacterial Isolates from Blind Tracheal Aspirates and Their Anti-Microbial Sensitivity: An Observational Study in ICU of a Tertiary Care Hospital in Bangladesh - Mallick, Uzzwal Kumar; Islam, Md Sirajul; Asaduzzaman, Mohammad; Yusuf, Mohammad Abdullah; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2020)
Background: The number of organisms developing resistance to commonly used antibiotics is increasing day by day. The exact national scenario of antimicrobial sensitivity pattern is not well known in Bangladesh owing to the absence of proper guideline for prescribing antibiotics. Aims: The aim of this study is to identify the group of organisms developing resistanceso that antibiotic policy can be formulated for the proper and effective use of antibiotics. Settings and Design: This observational study was conducted for a period of 1 year from January 2018 to December 2018 in a tertiary care hospital in Bangladesh. Materials and methods: This descriptive cross-sectional study was conducted in the Department of Microbiology, National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from January 2018 to December 2018, using the convenient sampling technique. Tracheal secretions from patients in the intensive care unit (ICU), tested in Department of Microbiology, National Institute of Neurosciences and Hospital, were included in the study. The culture was done on blood and MacConkey agar and the sensitivity pattern was performed on Muller Hinton agar. Data were analyzed using SPSS version 23.0. Results: Out of the microorganisms isolated from positive growth cultures, Acinetobacter (57.8%) was the most common isolate followed by Klebsiella (22.9%). Acinetobacter, pseudomonas and klebsiella had good sensitivity to colistin(87.80%, 82.40% and 77.80% respectively), where as they showed less sensitivity to higher generationcephalosporin, penicillin and aminoglycosides. Conclusion: The commonest organism which was isolated from the endotracheal aspirate cultures were Acinetobacter, followed by Pseudomonas and Klebsiella and antimicrobial susceptibility testing showed sensitivity to Colistin, Tazobactam/piperacillin, Meropenem and aztreonam. Whereas coagulase negative staphylococci was isolated only in minority cases with highest sensitivity to vancomycin and linezolid. Bangladesh Crit Care J September 2020; 8(2): 81-85